Jihadist expression in the scripts of the film "The Lion of the Desert" - Zaenal Masduqi; Sangidu Sangidu (Indonesian Journal of Arabic Studies, 2021)
This study is intended to describe the character of Omar Mukhtar visualized in the film entitled 'Lion of the Desert' and to analyze jihad expressions in the form of statements or questions in the film. This research has used a qualitative approach using narrative analysis method. The subject of this research is the film "The Lion of the Desert" by Moustapha Akkad, while the object of research is the narrative and dialogue of the scenes in the film which are related to the expression of jihad in the film "The Lion of the Desert". The technique of collecting data is by doing documentation techniques, the whole data is described and interpreted so as to produce a descriptive data discussion. The character of Omar Al-Mukhtar is shown in the film as a figure of a believer who holds fast to his religious values, he is also a devout patriot who always increases the fighting spirit of the Libyan people to be free from the grip of the Italian state colonialism. There are seven expressions found in the film's narrative as expressions of jihad, either explicitly or implicitly.